Residue hydrodemetallization catalyst and method for making same

CN122999237APending Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510570077.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但是,由于渣油中金属等杂原子的存在,使得渣油加氢催化剂在反应过程中易因金属和积碳的沉积而失活,而脱金属催化剂在固定床渣油加氢催化剂级配体系中的位置相对靠前,承担了较多的反应负荷,因此,开发一种寿命更长、加氢性能更好的加氢处理催化剂、尤其是加氢脱金属催化剂就显得尤为重要

Benefits of technology

[0071]本发明提供了一种渣油加氢脱金属催化剂的制备方法,首先在载体制备过程中引入部分助活性金属,让引入的部分助活性金属首先分散在氧化铝载体体相中,在焙烧过程中与氧化铝相互作用,不仅可以改善载体性质还可以降低催化剂表面的反应强度,增加大分子进一步进入催化剂内部的能力,然后对所得载体进行表面覆碳处理,最后再采用“内水相/油相/外水相”型浸渍液浸渍负载主活性金属和剩余助活性金属,其中主活性金属和剩余助活性金属均分散于内水相中。本发明方法通过各步骤的综合协调,最终制得的渣油加氢脱金属催化剂抗积碳性能、脱金属活性与容金属能力均大幅提高,能够保证装置的长周期稳定运行。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005386941620000141
    Figure BDA0005386941620000141
  • Figure BDA0005386941620000151
    Figure BDA0005386941620000151
  • Figure BDA0005386941620000152
    Figure BDA0005386941620000152
Patent Text Reader

Abstract

The application discloses a residual oil hydrodemetallization catalyst and a preparation method thereof. The preparation method of the catalyst comprises the following steps: (1) mixing an aluminum source, a first active metal, an alkaline additive and water, grinding, filtering, and obtaining a carrier precursor; (2) mixing the carrier precursor obtained in the step (1), an auxiliary extruding agent and a glue agent into a shape, drying, calcining, and then performing a surface carbon coating treatment to obtain a carrier; (3) impregnating the carrier obtained in the step (2) with an impregnation solution containing a main active metal and a second active metal, drying, and calcining to obtain the catalyst; wherein the impregnation solution comprises an inner water phase, an oil phase covering the inner water phase and an outer water phase, and the main active metal and the second active metal are distributed in the inner water phase. The catalyst has strong hydrogenation activity, and the carbon deposition resistance, the demetallization activity and the metal capacity are greatly improved, so that the long-period stable operation of the device can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a hydrogenation catalyst, specifically to a hydrogenation demetallization catalyst for the hydrotreating process of residual oil and its preparation method. Background Technology

[0002] With the increasing severity and deterioration of crude oil quality, coupled with the growing market demand for light oil products, heavy oil hydrotreating technology has gradually become a focus of attention in the petrochemical industry. Fixed-bed residue hydrotreating technology is mature and widely applied, serving as a crucial means to achieve clean and efficient utilization of vacuum residue. However, the presence of metals and other heteroatoms in the residue makes hydrotreating catalysts prone to deactivation during the reaction process due to metal and carbon deposition. Since demetallization catalysts occupy a relatively prominent position in the fixed-bed residue hydrotreating catalyst gradation system and bear a significant reaction load, developing a hydrotreating catalyst with a longer lifespan and better hydrotreating performance, especially a hydrodemetallization catalyst, is of paramount importance.

[0003] Currently, research on hydrogenation demetallization catalysts mainly focuses on the pore size of the support, such as introducing pore-expanding agents and acid treatment during the support preparation process. However, the acidity distribution on the surface of the support prepared by these methods is uneven, and the introduction of additives destroys the original pores of the support, which is not conducive to the dispersion of active metals in the subsequent impregnation process. As a result, the catalyst has poor hydrogenation performance, poor resistance to metal deposition, and poor resistance to carbon buildup.

[0004] CN104646007A discloses a residue oil hydrodemetallization catalyst and its preparation and application. First, an activated carbon support undergoes two pretreatment processes: hydrochloric acid washing and nitric acid oxidation. Then, a composite additive, activated carbon, and alumina are mixed and extruded to prepare an activated carbon / alumina composite. Finally, metal is loaded onto the support using a hydrotalcite method, i.e., an equal volume of a mixed solution of terephthalic acid, nickel nitrate, urea, and ammonium nitrate in a molar ratio of 2:1:(2.5-5):(1-5) is impregnated. Crystallization is performed, followed by several washings and drying to obtain nickel-salt talc microcrystals. These microcrystals are then placed in a Mo salt solution for complete displacement, filtered, washed, and the resulting green solid particles are dried and calcined to obtain the residue oil hydrodemetallization catalyst. The hydrodemetallization activity and stability of the hydrodemetallization catalyst prepared by the above method require further improvement. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a catalyst for the hydrodemetallization of heavy and residual oils and its preparation method. When used in the hydrodemetallization reaction of heavy and residual oils, this catalyst exhibits strong hydrogenation activity, significantly improved anti-carbon deposition performance, demetallization activity, and metal-containing capacity, ensuring long-term stable operation of the equipment.

[0006] The first aspect of this invention provides a method for preparing a hydrodemetallization catalyst for residue oil, comprising the following steps:

[0007] (1) Mix aluminum source, first active metal, alkaline additive and water, grind and filter to obtain carrier precursor;

[0008] (2) The carrier precursor, extrusion aid and adhesive obtained in step (1) are mixed and shaped, dried and calcined, and then the surface is carbonized to obtain the carrier.

[0009] (3) Impregnate the carrier obtained in step (2) with an impregnation solution containing the main active metal and the second auxiliary active metal, dry and calcine to obtain the catalyst; wherein the impregnation solution includes an inner aqueous phase, an oil phase covering the inner aqueous phase and an outer aqueous phase, and the main active metal and the second auxiliary active metal are distributed in the inner aqueous phase.

[0010] Furthermore, the inner aqueous phase further includes a co-emulsifier, a water-soluble polymer, and water, as well as optional additives; the outer aqueous phase includes a hydrophilic agent and water; and the oil phase includes a surfactant and oil.

[0011] Further, in step (1), the aluminum source is preferably boehmite, which is prepared using conventional methods, such as the aluminum sulfate method, the aluminum alkoxide method, or the sol-gel method. The alumina content in the boehmite is 60.0% to 75.0% by mass.

[0012] Further, in step (1), the alkaline auxiliary agent is one or more alkaline compounds such as sodium hydroxide, potassium hydroxide, and sodium carboxylate (e.g., sodium acetate, sodium formate).

[0013] Further, in step (1), the first auxiliary active metal is selected from at least one of Group VIII metals, preferably Ni and / or Co. The Group VIII metal source is selected from at least one of basic nickel carbonate, nickel sulfate, nickel nitrate, cobalt nitrate, etc.

[0014] Further, in step (1), the mass ratio of aluminum source (calculated as alumina), first auxiliary active metal (calculated as oxide), alkaline auxiliary agent, and water is 200-240: 1.0-10.0: 6.0-15.0: 120-180.

[0015] Furthermore, in step (1), the grinding can be performed using methods such as ball milling or sand milling. The ground material not only exhibits more uniform metal dispersion, but the alkaline additive also forms a "first protective film" on the surface of the dried material. The filtration process is a standard procedure in the art. After grinding, a ground sample with an average particle size of 2.0–10.0 μm is obtained.

[0016] Furthermore, in step (1), the first auxiliary active metal can interact with the support during the calcination process to weaken the acidity of the support, and can also work synergistically with the main active metal (preferably Mo) to facilitate the hydrogenation reaction.

[0017] Further, in step (2), the adhesive can be an organic acid and / or an inorganic acid. The inorganic acid can be one or more of nitric acid, sulfuric acid, boric acid, and phosphoric acid, and the organic acid can be one or more of tartaric acid, citric acid, and oxalic acid. The mass of the adhesive is 0.5% to 5.0% of the aluminum source in step (1) based on alumina. The extrusion aid can be one or more of methylcellulose, ethylcellulose, guar gum, and starch. The mass of the extrusion aid added is 0.5% to 8.0% of the aluminum source based on alumina. Further, water can be added during the molding process, and the amount of water is 80% to 120% of the aluminum source in step (1) based on alumina.

[0018] Furthermore, in step (2), the forming method can be at least one of extrusion, sheeting, and ball forming. The formed shape can be clover-shaped, four-leaf clover-shaped, butterfly-shaped, cylindrical, spherical, or strip-shaped, etc.

[0019] Further, in step (2), after molding, the substrate is first dried and then calcined to obtain a pre-carrier, and then subjected to surface carbon coating treatment. Further, the drying temperature is 120–200℃, and the drying time is 2–12 hours. The calcination process employs a two-stage calcination process: the first stage calcination temperature is 350–450℃, the calcination time is 2–6 hours, and the calcination atmosphere is one or more of air, nitrogen, or water vapor, preferably air; the second stage calcination temperature is 450–750℃, the calcination time is 2–8 hours, and the calcination atmosphere is one or more of air, nitrogen, or water vapor, preferably nitrogen. Preferably, the second stage calcination temperature is 150–300℃ higher than the first stage calcination temperature.

[0020] Further, in step (2), the carbon coating treatment uses an aqueous emulsion containing a polymer compound and water-soluble cellulose. In the aqueous emulsion, the polymer compound has a mass content of 5.0% to 15.0%, and the water-soluble cellulose has a mass content of 0.5% to 3.0%.

[0021] Furthermore, the polymer compound is not particularly limited and may be selected from one or more of polyimide, polyfurfuryl alcohol, and phenolic resin. The water-soluble cellulose is one or more of hydroxymethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose.

[0022] Furthermore, the ratio of the aqueous emulsion (by volume mL) to the pre-carrier (by mass g) is 0.8–1.5 mL / g.

[0023] Further, after the surface carbonization treatment, the carrier is first subjected to conventional filtration, washing, drying, and calcination to obtain the carrier. The drying temperature is 120-200℃, and the drying time is 2.0-12.0h. The calcination conditions are: temperature 500-700℃, time 2.0-8.0h, and the calcination atmosphere is an inert atmosphere, preferably one or more of nitrogen and argon.

[0024] Further, in step (3), the mass ratio of surfactant to oil in the oil phase is 1.0:0.1 to 10, preferably 1.0:2.0 to 10.0, and more preferably 1.0:4.0 to 10.0, for example 1.0:4.0, 1.0:4.5, 1.0:5.0, 1.0:5.5, 1.0:6.0, 1.0:6.5, 1.0:7.0, 1.0:7.5, 1.0:8.0, 1.0:8.5, 1.0:9.0, 1.0:9.5, 1.0:10.0, etc., and any value within the range formed by any two of these values.

[0025] Further, in step (3), the mass ratio of the internal aqueous phase to the oil phase in the impregnation solution is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, 9.0:1.0, etc., and any value within the range formed by any two of these values.

[0026] Further, in step (3), the mass ratio of the "inner aqueous phase / oil phase" to the outer aqueous phase in the impregnation solution is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, etc., and any value within any range formed by any two of these values. The mass of the "inner aqueous phase / oil phase" refers to the total mass of the inner aqueous phase and the oil phase coating the inner aqueous phase.

[0027] Further, in step (3), the water-soluble polymer in the internal aqueous phase is one or more of polyvinyl alcohol (molecular weight 170,000 to 220,000), carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate (molecular weight less than 10,000).

[0028] Furthermore, in step (3), the mass concentration of the water-soluble polymer in the internal aqueous phase is 4.0% to 14.0%.

[0029] Further, in step (3), the concentration of Group VIB metals as oxides in the internal aqueous phase is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; the concentration of Group VIII metals as oxides is 2-50 g / 100 mL, preferably 5-30 g / 100 mL.

[0030] Further, in step (3), in the internal aqueous phase, the primary active metal is selected from at least one of Group VIB metals, preferably Mo and / or W; the second auxiliary active metal is selected from at least one of Group VIII metals, preferably Ni and / or Co. The Group VIB metal source is one or more of ammonium molybdate, ammonium metatungstate, and molybdenum oxide; the Group VIII metal source is one or more of basic nickel nitrate, nickel sulfate, nickel nitrate, and cobalt nitrate.

[0031] Further, in step (3), the auxiliary agent in the internal aqueous phase is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus; the phosphorus source is one or more of phosphoric acid, ammonium hydrogen phosphate, and ammonium dihydrogen phosphate. In the internal aqueous phase, the concentration of the auxiliary agent, calculated as oxide, is 0-15.0 g / 100 mL, preferably 0.5-10.0 g / 100 mL.

[0032] Further, in step (3), the co-emulsifier in the inner aqueous phase is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecyl alcohol, propylene glycol, n-butanol, and glycerin. The mass concentration of the co-emulsifier in the inner aqueous phase is 0.5% to 5.0%.

[0033] Further, in step (3), the hydrophilic agent in the external aqueous phase is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide. The mass concentration of the hydrophilic agent in the external aqueous phase is 4.0–15.0%.

[0034] Further, in step (3), the surfactant in the oil phase is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(OCC)). x-OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11, etc., one or more of the following: The oil is selected from at least one of silicone oil and vegetable oil; the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methylphenyl silicone oil. The vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.

[0035] Further, the method for preparing the impregnation solution containing the primary active metal and the secondary auxiliary active metal includes:

[0036] (a) Mix the co-emulsifier, the main active metal source, water and optional auxiliary source, and heat to obtain a clear solution;

[0037] (b) The second co-active metal source, the water-soluble polymer, and the clear solution obtained in step (a) are mixed to obtain an internal aqueous phase;

[0038] (c) The aqueous phase from step (b) is added dropwise to the oil phase to obtain an "aqueous phase / oil phase" emulsion.

[0039] (d) Mix the hydrophilic agent and water to obtain the external aqueous phase;

[0040] (e) The “inner aqueous phase / oil phase” type emulsion obtained in step (c) is added dropwise to the outer aqueous phase obtained in step (d) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution, that is, an impregnation solution containing a primary active metal and a secondary auxiliary active metal.

[0041] Further, in step (a), the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, polyvinyl alcohol, and glycerin.

[0042] Further, in step (a), the amount of the co-emulsifier is 0.5% to 5.0% of the mass of the internal aqueous phase obtained in step (b).

[0043] Further, in step (a), the main active metal is selected from at least one of Group VIB metals, preferably molybdenum, and the molybdenum source can be one or more of molybdenum oxide, ammonium tetramolybdate, ammonium heptamolybdate, etc. The auxiliary agent is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus; the phosphorus source can be one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, etc.

[0044] Further, in step (a), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.

[0045] Further, in step (a), the heating is carried out to a temperature of 90-120°C so that the substances added in step (2) are mixed evenly to form a clear solution.

[0046] Further, in step (b), the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate.

[0047] Further, in step (b), the second auxiliary active metal is selected from at least one of Group VIII metals, preferably Ni and / or Co. The Group VIII metal source is one or more of basic nickel carbonate, cobalt nitrate, etc.

[0048] Further, in step (b), the mass concentration of the water-soluble polymer in the aqueous phase obtained in step (b) is 4.0% to 14.0%.

[0049] Further, in step (b), the concentration of Group VIB metals as oxides in the internal aqueous phase is 8-80 g / 100 mL, preferably 10-60 g / 100 mL, the concentration of Group VIII metals as oxides is 2-50 g / 100 mL, preferably 5-30 g / 100 mL, and the concentration of additives as oxides is 0-15.0 g / 100 mL, preferably 0.5-10.0 g / 100 mL.

[0050] Further, in step (c), the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0.

[0051] Further, in step (c), the oil phase includes a surfactant and oil, wherein the mass ratio of the surfactant to the oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0.

[0052] Further, in step (c), the surfactant is selected from one or more of glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (with the structure R-(OCC)x-OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms and x is 2 to 11). The oil can be at least one of silicone oil and vegetable oil. The silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil. The vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.

[0053] Further, in step (c), the oil phase is in a liquid state. The oil phase is maintained at a temperature of 45–85°C, and the stirring rate is 400–800 r / min.

[0054] Further, in step (c), the preparation process of the oil phase includes: adding a surfactant to the oil and heating it to obtain the oil phase. The heating temperature is 45–85°C to make the oil phase present a homogeneous liquid state.

[0055] Furthermore, in step (c), during the dropwise addition of the internal aqueous phase to the oil phase, simultaneous stirring and shearing homogenization is performed. Furthermore, the stirring and shearing homogenization process is carried out at a stirring speed of 10000–18000 rpm, a homogenization time of 3–8 min, and a homogenization temperature of 50–85°C.

[0056] Further, in step (d), the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide.

[0057] Further, in step (d), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.

[0058] Further, in step (d), the mass concentration of the hydrophilic agent in the external aqueous phase is 4.0% to 15.0%.

[0059] Further, in step (e), the mass ratio of the "internal aqueous phase / oil phase" emulsion to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0.

[0060] Furthermore, in step (3), the impregnation method is saturated impregnation.

[0061] Furthermore, in step (3), the drying temperature is 120-200℃ and the drying time is 2-12h.

[0062] Further, in step (3), the roasting process is carried out at a temperature of 550 to 750°C and a roasting time of 2 to 10 hours. The roasting is carried out in a mixed atmosphere of air and water vapor, wherein the volume ratio of air to water vapor is 0.1 to 5.0:1.0.

[0063] A second aspect of the present invention provides a residue oil hydrodemetallization catalyst prepared by the above method.

[0064] Furthermore, in the catalyst, the first co-active metal is dispersed in the alumina support phase; the mass ratio of the first co-active metal, as an oxide, to the alumina support is 0.01 to 0.10:1, for example, but not limited to, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.10:1, etc., and any value within the range formed by any two of these values.

[0065] Furthermore, the first and second co-active metals are each independently selected from at least one group VIII metal, preferably Ni and / or Co. The main active metal is selected from at least one group VIB metal, preferably Mo and / or W.

[0066] Furthermore, based on the mass of the catalyst, the content of Group VIB metal oxides is 10.0%–16.0%, and the content of Group VIII metal oxides is 2.0%–7.0%. The mass ratio of Group VIII metal oxides in the first co-active metal component to that in the second co-active metal component is 0.5–5.0:1.

[0067] Furthermore, the specific surface area of ​​the catalyst is 170–190 m². 2 / g, with a pore volume of 0.55–0.85 mL / g; preferably, the catalyst has a specific surface area of ​​170–185 m² / g. 2 / g, with a pore volume of 0.65~0.80mL / g.

[0068] Furthermore, the catalyst also includes an auxiliary agent selected from at least one of phosphorus, silicon, or boron, preferably phosphorus. Furthermore, the auxiliary agent, based on the mass of the catalyst, comprises 2.0% to 6.0% in terms of oxides.

[0069] The third aspect of this invention provides the application of the above-mentioned catalyst in the hydrotreating of heavy oil and residual oil.

[0070] Compared with the prior art, the present invention has the following beneficial effects:

[0071] This invention provides a method for preparing a residue oil hydrodemetallization catalyst. First, a portion of co-active metal is introduced during the support preparation process. This co-active metal is initially dispersed in the alumina support bulk phase and interacts with the alumina during calcination. This not only improves the support properties but also reduces the reaction intensity on the catalyst surface, increasing the ability of macromolecules to further penetrate the catalyst interior. Then, the resulting support undergoes a surface carbonization treatment. Finally, the main active metal and the remaining co-active metal are impregnated using an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution, wherein both the main active metal and the remaining co-active metal are dispersed in the inner aqueous phase. Through the comprehensive coordination of each step, this invention significantly improves the residue oil hydrodemetallization catalyst's resistance to carbon deposition, demetallization activity, and metal-containing capacity, ensuring long-term stable operation of the equipment.

[0072] In the catalyst preparation process of this invention, the addition of a first co-active metal (such as Ni) during grinding, combined with the introduced alkaline promoter, weakens the interaction between nickel and alumina during support formation. Then, the support is coated with a carbon film. After the carbon film is formed, it ensures that the subsequent main active metal (such as Mo) does not come into contact with the already loaded and dispersed first co-active metal during impregnation, while the main active metal is uniformly dispersed on the carbon film. Finally, after calcination in a mixed atmosphere, air is introduced to remove the carbon film, leaving the main active metal uniformly dispersed on the support. This method effectively avoids the problem of uneven distribution of active metals caused by competitive adsorption on the support surface during mixed impregnation of two metals. Furthermore, carbon coating is performed on the pre-support containing the first co-active metal, followed by calcination under an inert gas. Moisture gradually evaporates, and latex particles are gradually extruded to form a thin film containing crosslinkable groups, forming a three-dimensional network film. This film temporarily provides loading sites for the main active metal and the second co-active metal. After catalyst calcination, the film disappears, and the main and second co-active metals are uniformly dispersed on the pre-support, working in conjunction with the first co-active metal to improve the activity and stability of hydrodemetallization. To ensure high dispersion of the main and second co-active metals on the carbon film, this invention utilizes a surfactant to better disperse the prepared aqueous phase containing active metals (including the main and second co-active metals) in the oil phase. Further, an "aqueous / oil" emulsion is dispersed in the aqueous phase, forming an impregnation solution where the active metals are dispersed in the oil phase and then further dispersed in the aqueous phase—an "aqueous / oil / aqueous" impregnation solution. This allows for the preparation of catalysts with more uniform distribution of active metals inside and on the surface of the support. Specifically, the main active metal is first fully dispersed in the carrier water in ionic form using a co-emulsifier. Then, the co-active metal is dissolved in the solution to obtain an inner aqueous phase containing both the main and co-active metals. To control particle size and maintain particle size distribution during the subsequent formation of the "inner aqueous / oil phase" emulsion, a water-soluble polymer is added to the inner aqueous phase as a "protective layer" for the particles. This polymer adsorbs onto the particle surface during the emulsion formation, forming a surface layer of a certain thickness that effectively hinders particle collisions and aggregation, further improving the system's stability. Then, under specific conditions, the "inner aqueous / oil phase" emulsion is dispersed in an outer aqueous phase to obtain an impregnation solution containing both the main and second co-active metals.

[0073] The present invention employs an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution, utilizing the highly dispersed properties of the inner aqueous phase in the oil phase and the highly dispersed properties of the "inner aqueous phase / oil phase" in the outer aqueous phase. The inner aqueous phase serves as the carrier matrix for the active metal components, while the oil phase uniformly disperses the metals in the inner aqueous phase on the surface and in the pores of the carrier. In this invention, the highly dispersed small droplets can penetrate deep into the pores and surface of the carbon film. Furthermore, during the calcination of the catalyst in a mixed atmosphere, the distribution of the active metals in the catalyst is optimized during the removal of the carbon layer by air. The comprehensive coordination of each step improves the catalyst activity and stability. Detailed Implementation

[0074] The technical solutions and effects of the present invention will be further illustrated below with reference to the embodiments, but the invention is not limited to the following embodiments.

[0075] In this invention, the pore structure and specific surface area of ​​the catalyst are characterized using the Mack ASAP-2420 physical adsorption instrument.

[0076] Unless otherwise specified, all experimental materials used in this invention were purchased from conventional biochemical reagent manufacturers.

[0077] Example 1

[0078] In this example, the preparation method of the impregnation solution containing the primary active metal Mo and the secondary auxiliary active metal Ni includes:

[0079] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:8.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is hexadecyltrimethylamine bromide. The mass ratio of co-emulsifier, molybdenum source (calculated as molybdenum oxide), phosphorus source (calculated as phosphorus oxide), nickel source (calculated as nickel oxide), and water-soluble polymer to water is 20:265:60.8:58.7:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:0.7. The mass ratio of hydrophilic agent to water is 10:100. The mass ratio of "internal aqueous phase / oil phase" type emulsion to external aqueous phase is 0.9:1.0.

[0080] The surfactant glyceryl monostearate was added to the silicone oil and heated to 80°C until the silicone oil melted, thus obtaining the oil phase.

[0081] (a) Polyethylene glycol-8000, molybdenum oxide, and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 500 r / min. When the temperature was raised to 120°C, it was maintained for 4 hours. A constant stirring speed was maintained until a clear solution was obtained.

[0082] (b) First, add basic nickel carbonate to the clear solution obtained in step (a), and then add water-soluble polymer polyvinyl alcohol to obtain an inner aqueous phase;

[0083] (c) The aqueous phase from step (b) is added dropwise to the oil phase. During the addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" emulsion is obtained.

[0084] (d) Add the hydrophilic agent to the water to obtain the external aqueous phase;

[0085] (e) The “inner aqueous phase / oil phase” type emulsion obtained in step (c) is added dropwise to the outer aqueous phase obtained in step (d) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution, that is, an impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni.

[0086] In this example, the catalyst preparation method includes:

[0087] (1) 300g of boehmite (alumina content 74.0%), 15.4g of basic nickel carbonate (nickel oxide content 52.0%), 12.5g of alkaline additive NaOH, and 160g of deionized water were mixed, ground (the average particle size of the sample after grinding was 5.0μm), and filtered to obtain the carrier precursor.

[0088] (2) The carrier precursor obtained in step (1) is mixed with 9.4g of nitric acid, 6.0g of guar gum powder, and 180g of deionized water, and then extruded into a four-leaf clover shape. It is dried at 120℃ for 6h and calcined (the first calcination temperature is 400℃, the calcination time is 3h, and the calcination atmosphere is air; the second calcination temperature is 600℃, the calcination time is 4h, and the calcination atmosphere is nitrogen) to obtain a Ni-containing precarrier. Then, the obtained Ni-containing precarrier is mixed evenly with an aqueous emulsion containing polyimide and hydroxymethyl cellulose. The mass content of polyimide in the aqueous emulsion is 8.0%, the mass content of hydroxymethyl cellulose is 0.8%, and the ratio of the volume of the aqueous emulsion (mL) to the precarrier (g) is 1.0mL / g. Then, it is dried at 150℃ for 8h and calcined at 650℃ for 5h under a nitrogen atmosphere to obtain the carrier.

[0089] (3) The carrier obtained in step (2) is impregnated with an impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni in a saturated impregnation manner. It is first dried at 150°C for 4 hours, and then calcined at 600°C for 4 hours in a mixed atmosphere of air and water vapor (the volume ratio of air and water vapor is 1:2) to obtain catalyst CAT-1.

[0090] Example 2

[0091] In this example, the preparation method of the impregnation solution containing the primary active metal Mo and the secondary auxiliary active metal Ni includes:

[0092] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:8.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is hexadecyltrimethylamine bromide. The mass ratio of co-emulsifier, molybdenum source (calculated as molybdenum oxide), phosphorus source (calculated as phosphorus oxide), nickel source (calculated as nickel oxide), and water-soluble polymer to water is 20:265:60.8:48.7:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:0.7. The mass ratio of hydrophilic agent to water is 10:100. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 0.9:1.0.

[0093] The surfactant glyceryl monostearate was added to the silicone oil and heated to 80°C until the silicone oil melted, thus obtaining the oil phase.

[0094] (a) Polyethylene glycol-8000, molybdenum oxide, and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 500 r / min. When the temperature was raised to 120°C, it was maintained for 4 hours. A constant stirring speed was maintained until a clear solution was obtained.

[0095] (b) First, add basic nickel carbonate to the clear solution obtained in step (a), and then add water-soluble polymer polyvinyl alcohol to obtain an inner aqueous phase;

[0096] (c) The aqueous phase from step (b) is added dropwise to the oil phase. During the addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" emulsion is obtained.

[0097] (d) Add the hydrophilic agent to the water to obtain the external aqueous phase;

[0098] (e) The “inner aqueous phase / oil phase” type emulsion obtained in step (c) is added dropwise to the outer aqueous phase obtained in step (d) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution, that is, an impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni.

[0099] In this example, the catalyst preparation method includes:

[0100] (1) Mix 300g of boehmite (alumina content 74.0%), 15.0g of basic nickel carbonate (nickel oxide content 52.0%), 10.5g of alkaline additive NaOH, and 150g of deionized water, grind (the average particle size of the sample after grinding is 5.0μm), filter, and obtain the carrier precursor;

[0101] (2) The carrier precursor obtained in step (1) is mixed with 9.4g of nitric acid, 8.0g of guar gum powder, and 190g of deionized water, and then extruded into a four-leaf clover shape. It is dried at 140℃ for 4h and calcined (the first calcination temperature is 450℃, the calcination time is 3h, and the calcination atmosphere is air; the second calcination temperature is 700℃, the calcination time is 4h, and the calcination atmosphere is nitrogen) to obtain a Ni-containing precarrier. Then, the obtained Ni-containing precarrier is mixed evenly with an aqueous emulsion containing polyimide and hydroxymethyl cellulose. The mass content of polyimide in the aqueous emulsion is 8.0%, the mass content of hydroxymethyl cellulose is 0.8%, and the ratio of the volume of the aqueous emulsion (mL) to the precarrier (g) is 1.0mL / g. Then, it is dried at 150℃ for 8h and calcined at 650℃ for 5h under a nitrogen atmosphere to obtain the carrier.

[0102] (3) The carrier obtained in step (2) is impregnated with an impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni in a saturated impregnation manner. It is first dried at 150°C for 4 hours, and then calcined at 600°C for 4 hours in a mixed atmosphere of air and water vapor (the volume ratio of air and water vapor is 1:2) to obtain catalyst CAT-2.

[0103] Example 3

[0104] The impregnation solution in this example, containing the primary active metal Mo and the secondary active metal Ni, is the same as in Example 1.

[0105] In this example, the catalyst preparation method includes:

[0106] (1) 300g of boehmite (alumina content 74.0%), 15.4g of basic nickel carbonate (nickel oxide content 52.0%), 12.5g of alkaline additive NaOH, and 160g of deionized water were mixed, ground (the average particle size of the sample after grinding was 5.0μm), and filtered to obtain the carrier precursor.

[0107] (2) The carrier precursor obtained in step (1) is mixed with 9.4g of nitric acid, 6.0g of guar gum powder, and 180g of deionized water, then extruded into a four-leaf clover shape, dried at 120℃ for 6h, and calcined (the first calcination temperature is 400℃, the calcination time is 3h, and the calcination atmosphere is air; the second calcination temperature is 600℃, the calcination time is 4h, and the calcination atmosphere is nitrogen) to obtain a Ni-containing pre-carrier; the pre-carrier is mixed evenly with an aqueous emulsion containing polyimide and hydroxymethyl cellulose, dried at 140℃ for 6h, and calcined at 600℃ for 4h under a nitrogen atmosphere to obtain the carrier; wherein, the mass content of polyimide in the aqueous emulsion is 12.0%, and the mass content of hydroxymethyl cellulose is 1.5%; the ratio of the amount of aqueous emulsion (by volume mL) to the amount of pre-carrier (by mass g) is 1.2mL / g;

[0108] (3) The carrier obtained in step (2) is impregnated with an impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni in a saturated impregnation manner. It is first dried at 140°C for 6 hours, and then calcined at 600°C for 4 hours in a mixed atmosphere of air and water vapor (the volume ratio of air and water vapor is 2:3) to obtain catalyst CAT-3.

[0109] Example 4

[0110] In this example, the preparation method of the impregnation solution containing the primary active metal Mo and the secondary auxiliary active metal Ni includes:

[0111] The surfactant is glyceryl distearate, the silicone oil is ethyl silicone oil, and the surfactant to silicone oil mass ratio is 1.0:8.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is hexadecyltrimethylamine bromide. The mass ratio of co-emulsifier, molybdenum source (calculated as molybdenum oxide), phosphorus source (calculated as phosphorus oxide), nickel source (calculated as nickel oxide), and water-soluble polymer to water is 20:265:61.1:59.0:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:4.0. The mass ratio of hydrophilic agent to water is 10:100. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 3.0:1.0.

[0112] The surfactant glyceryl monostearate was added to the silicone oil and heated to 80°C until the silicone oil melted, thus obtaining the oil phase.

[0113] (a) Polyethylene glycol-8000, molybdenum oxide, and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 500 r / min. When the temperature was raised to 120°C, it was maintained for 4 hours. A constant stirring speed was maintained until a clear solution was obtained.

[0114] (b) First, add basic nickel carbonate to the clear solution obtained in step (a), and then add water-soluble polymer polyvinyl alcohol to obtain an inner aqueous phase;

[0115] (c) The aqueous phase from step (b) is added dropwise to the oil phase. During the addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" emulsion is obtained.

[0116] (d) Add the hydrophilic agent to the water to obtain the external aqueous phase;

[0117] (e) The “inner aqueous phase / oil phase” type emulsion obtained in step (c) is added dropwise to the outer aqueous phase obtained in step (d) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution, that is, an impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni.

[0118] In this example, the catalyst was prepared according to the method in Example 1, and the final catalyst CAT-4 was obtained.

[0119] Comparative Example 1

[0120] Compared with Example 1, the difference is that no alkaline additive is introduced in the preparation process of the support precursor containing the first co-active metal in step (1). The hydrogenation demetallization catalyst DCAT-1 is finally obtained.

[0121] Comparative Example 2

[0122] Compared with Example 1, the difference is that the process of surface carbonization treatment of the Ni-containing pre-support in step (2) is omitted. Instead, the support obtained in step (2) is directly impregnated with an impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni in a saturated impregnation manner. Finally, the hydrogenation demetallization catalyst DCAT-2 is obtained.

[0123] Comparative Example 3

[0124] Compared with Example 1, the difference is that the solution used in the carbon coating process in step (2) is changed to a glucose aqueous solution with a mass percentage of 10.2%, and the ratio of glucose aqueous solution (by volume mL) to the pre-support (by mass g) is 1.1 mL / g. The hydrogenation demetallization catalyst DCAT-3 was finally obtained.

[0125] Comparative Example 4

[0126] Compared with Example 1, the difference lies in that the first auxiliary active metal source, basic nickel carbonate, is not added in the preparation of the support precursor in step (1), and the amount of MoO3 introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni in step (3) is 100% of the total MoO3 loading in the catalyst, and the amount of NiO introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni is 100% of the total NiO loading in the catalyst. Finally, the hydrogenation demetallization catalyst DCAT-4 is obtained.

[0127] Comparative Example 5

[0128] Compared with Example 1, the difference is that in step (3), no water-soluble polymers are introduced during the preparation of the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the main active metal Mo and the second auxiliary active metal Ni. Finally, the hydrogenation demetallization catalyst DCAT-5 is obtained.

[0129] Comparative Example 6

[0130] Compared with Example 1, the difference lies in the preparation method of the impregnation solution containing the primary active metal Mo and the secondary auxiliary active metal Ni, which includes:

[0131] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:8.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is hexadecyltrimethylamine bromide. The mass ratio of co-emulsifier, molybdenum source (calculated as molybdenum oxide), phosphorus source (calculated as phosphorus oxide), nickel source (calculated as nickel oxide), and water-soluble polymer to water is 20:265:60.8:58.7:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:0.7. The mass ratio of hydrophilic agent to water is 10:100. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 0.9:1.0.

[0132] (1) Molybdenum oxide, basic nickel carbonate and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 500 r / min. When the temperature was raised to 120°C, it was maintained for 4 hours. The stirring speed was kept constant until a transparent and clear solution was obtained, and the internal aqueous phase was obtained.

[0133] (2) Add the hydrophilic agent to the water to obtain the external aqueous phase;

[0134] (3) Add surfactant, silicone oil, and co-emulsifier to the aqueous phase obtained in step (1) while stirring. The shear homogenization speed is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60℃. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.

[0135] (4) Add the “inner aqueous phase / oil phase” emulsion obtained in step (3) to the outer aqueous phase obtained in step (2) to obtain the “inner aqueous phase / oil phase / outer aqueous phase” impregnation solution.

[0136] The final product was DCAT-6, a catalyst for the hydrodemetallization of residual oil.

[0137] Table 1. Physicochemical properties and catalyst composition of each example of hydrodemetallization catalyst.

[0138] Serial Number Example 1 Example 2 Example 3 Example 4 Catalyst number CAT-1 CAT-2 CAT-3 CAT-4 <![CDATA[Specific surface area, m 2 / g]]> 177 182 175 174 <![CDATA[pore volume, cm 3 / g]]> 0.70 0.72 0.67 0.68 First active metal NiO, wt% 2.10 2.60 2.14 2.13 <![CDATA[Al2O3,wt%]]> 80.17 80.08 80.16 80.1 Second active metal <![CDATA[MoO3,wt%]]> 12.21 12.24 12.21 12.23 NiO, wt% 2.71 2.24 2.70 2.72 <![CDATA[P2O5,wt%]]> 2.81 2.84 2.79 2.82

[0139] Table 2 Physicochemical properties and catalyst composition of each comparative example of hydrogenation demetallization catalyst

[0140] Serial Number Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Catalyst number DCAT-1 DCAT-2 DCAT-3 DCAT-4 DCAT-5 DCAT-6 <![CDATA[specific surface area, m 2 / g]]> 159 157 161 156 152 153 <![CDATA[pore volume, cm 3 / g]]> 0.63 0.64 0.60 0.64 0.61 0.59 First active metal NiO, wt% 2.13 2.15 2.12 0 2.13 2.10 <![CDATA[Al2O3,wt%]]> margin margin margin margin margin margin Second active metal <![CDATA[MoO3,wt%]]> 12.22 12.24 12.20 12.23 12.18 12.16 NiO, wt% 2.68 2.65 2.64 4.80 2.65 2.69 <![CDATA[P2O5,wt%]]> 2.80 2.78 2.74 2.79 2.75 2.77

[0141] Evaluation test

[0142] Activity stability tests were conducted on Examples 1-4 and Comparative Examples 1-6 using a 200mL fixed-bed hydrogenation test apparatus. The feedstock was residue oil with a density of 986.4 kg / m³. 3 (20℃), S content 2.42wt%, Ni and V contents 28.7μg / g and 58.1μg / g respectively, CCR content 12.2wt%, the demetallization rate after 2000h of operation in Example 1 was 100%, and all others were relative demetallization rates. Specific experimental conditions are shown in Table 3, and experimental results are shown in Tables 4 and 5.

[0143] Table 3 Experimental conditions

[0144] Reaction temperature, °C 380 Reaction pressure, MPa 15.7 <![CDATA[Liquid hourly volume space velocity, h -1 > 1.0 Hydrogen-to-oil ratio, V / V 750

[0145] Table 4. Test results of the hydrogenation demetallization catalysts in each example.

[0146]

[0147]

[0148] Table 5. Experimental results of hydrogenation demetallization catalysts in each comparative example.

[0149]

[0150] As can be seen from Tables 1-5, the hydrodemetallization catalyst prepared according to the method of the present invention has a high specific surface area and pore volume, as well as high hydrogenation activity and stability, and can well meet the requirements of the hydrodemetallization process of heavy and residual oils.

Claims

1. A method for preparing a residue oil hydrodemetallization catalyst, comprising the following steps: (1) Mix aluminum source, first active metal, alkaline additive and water, grind and filter to obtain carrier precursor; (2) The carrier precursor, extrusion aid and adhesive obtained in step (1) are mixed and shaped, dried and calcined, and then the surface is carbonized to obtain the carrier. (3) The support obtained in step (2) is impregnated with an impregnation solution containing the main active metal and the second auxiliary active metal, dried, and calcined to obtain the catalyst; wherein, The impregnation solution includes an inner aqueous phase, an oil phase that coats the inner aqueous phase, and an outer aqueous phase, wherein the main active metal and the second auxiliary active metal are distributed in the inner aqueous phase.

2. The preparation method according to claim 1, characterized in that, In step (1), the aluminum source is boehmite; and / or, the mass content of alumina in the boehmite is 60.0% to 75.0%; And / or, in step (1), the first auxiliary active metal is selected from at least one of Group VIII metals, preferably Ni and / or Co; And / or, in step (1), the alkaline additive is one or more of sodium hydroxide, potassium hydroxide, and sodium carboxylate.

3. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of aluminum source (calculated as alumina), first auxiliary active metal (calculated as oxide), alkaline auxiliary agent, and water is 200-240: 1.0-10.0: 6.0-15.0: 120-180.

4. The preparation method according to claim 1, characterized in that, In step (2), the adhesive is an organic acid and / or an inorganic acid, wherein the inorganic acid is one or more of nitric acid, sulfuric acid, boric acid, and phosphoric acid, and the organic acid is one or more of tartaric acid, citric acid, and oxalic acid; and / or, the extrusion aid is one or more of methylcellulose, ethylcellulose, guar gum powder, and starch.

5. The preparation method according to claim 1, characterized in that, In step (2), the mass of the adhesive is 0.5% to 5.0% of the mass of the aluminum source in step (1) based on alumina; and / or, the mass of the extrusion aid is 0.5% to 8.0% of the mass of the aluminum source based on alumina.

6. The preparation method according to claim 1, characterized in that, In step (2), the roasting adopts a two-stage roasting process. The first stage roasting temperature is 350-450℃, the roasting time is 2-6h, and the roasting atmosphere is one or more of air, nitrogen, or water vapor, preferably air. The second stage roasting temperature is 450-750℃, the roasting time is 2-8h, and the roasting atmosphere is one or more of air, nitrogen, or water vapor, preferably nitrogen. Preferably, the second stage roasting temperature is 150-300℃ higher than the first stage roasting temperature.

7. The preparation method according to claim 1, characterized in that, In step (2), the carbon coating treatment uses an aqueous emulsion containing a polymer compound and water-soluble cellulose; the polymer compound is one or more of polyimide, polyfurfuryl alcohol, and phenolic resin; the water-soluble cellulose is one or more of hydroxymethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose.

8. The preparation method according to claim 7, characterized in that, The aqueous emulsion contains 5.0% to 15.0% by mass of polymeric compounds and 0.5% to 3.0% by mass of water-soluble cellulose. And / or, the ratio of the volume of the aqueous emulsion (mL) to the mass of the pre-carrier (g) is 0.8–1.5 mL / g.

9. The preparation method according to claim 1, characterized in that, In step (3), the concentration of Group VIB metals as oxides in the internal aqueous phase is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; the concentration of Group VIII metals as oxides is 2-50 g / 100 mL, preferably 5-30 g / 100 mL.

10. The preparation method according to claim 1, characterized in that, In step (3), the impregnation solution includes an inner aqueous phase comprising a co-emulsifier, a water-soluble polymer, and water, as well as optional additives; an outer aqueous phase comprising a hydrophilic agent and water; and an oil phase comprising a surfactant and oil.

11. The preparation method according to claim 10, characterized in that, In the oil phase, the mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0; And / or, in the impregnation solution, the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0; And / or, in the impregnation solution, the mass ratio of the "inner aqueous phase / oil phase" to the outer aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.

0.

12. The preparation method according to claim 10, characterized in that, In the internal aqueous phase, the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate. And / or, in the internal aqueous phase, the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol and glycerin; And / or, in the internal aqueous phase, the additive is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus.

13. The preparation method according to claim 10 or 12, characterized in that, In the internal aqueous phase, the mass concentration of water-soluble polymer is 4.0% to 14.0%; And / or, in the internal aqueous phase, the mass concentration of the co-emulsifier is 0.5% to 5.0%; And / or, in the internal aqueous phase, the concentration of the additive, calculated as oxide, is 0 to 15.0 g / 100 mL, preferably 0.5 to 10.0 g / 100 mL.

14. The preparation method according to claim 10, characterized in that, In the external aqueous phase, the hydrophilic agent is one or more of the following: polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide. Preferably, the mass concentration of the hydrophilic agent in the external aqueous phase is 4.0% to 15.0%.

15. The preparation method according to claim 10, characterized in that, In the oil phase, the surfactant is selected from one or more of glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol; the oil is selected from at least one of silicone oil and vegetable oil, wherein the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.

16. The preparation method according to claim 1, characterized in that, The method for preparing the impregnation solution containing the primary active metal and the secondary auxiliary active metal includes: (a) Mix the co-emulsifier, the main active metal source, water and optional auxiliary source, and heat to obtain a clear solution; (b) The second co-active metal source, the water-soluble polymer, and the clear solution obtained in step (a) are mixed to obtain an internal aqueous phase; (c) The aqueous phase from step (b) is added dropwise to the oil phase to obtain an "aqueous phase / oil phase" emulsion. (d) Mix the hydrophilic agent and water to obtain the external aqueous phase; (e) The "inner aqueous phase / oil phase" type emulsion obtained in step (c) is added dropwise to the outer aqueous phase obtained in step (d) to obtain an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution, that is, an impregnation solution containing a primary active metal and a secondary auxiliary active metal.

17. The preparation method according to claim 16, characterized in that, In step (a), the heating temperature is 90–120°C; And / or, in step (c), the oil phase is in a liquid state; the oil phase is kept in a liquid state at a temperature of 45–85°C and a stirring rate of 400–800 r / min.

18. The preparation method according to claim 16, characterized in that, In step (c), during the process of adding the internal aqueous phase to the oil phase, stirring and shearing homogenization are carried out simultaneously. Preferably, the stirring-shear homogenization process has a stirring speed of 10,000 to 18,000 rpm, a homogenization time of 3 to 8 minutes, and a homogenization temperature of 50 to 85°C.

19. The preparation method according to claim 1, characterized in that, In step (3), the roasting process is carried out at a temperature of 550 to 750°C and a roasting time of 2 to 10 hours. The roasting is carried out in a mixed atmosphere of air and water vapor, wherein the volume ratio of air to water vapor is 0.1 to 5.0:1.

0.

20. The residue hydrodemetallization catalyst prepared by any one of the preparation methods described in claims 1-19.

21. The catalyst according to claim 20, characterized in that, In the catalyst, the first co-active metal is dispersed in the alumina support phase; the mass ratio of the first co-active metal (calculated as oxide) to the alumina support is 0.01 to 0.10:

1. Preferably, the first and second auxiliary active metals are each independently selected from at least one group VIII metal, preferably Ni and / or Co; the main active metal is selected from at least one group VIB metal, preferably Mo and / or W.

22. The catalyst according to claim 21, characterized in that, Based on catalyst mass, the content of Group VIB metal oxides is 10.0%–16.0%, and the content of Group VIII metal oxides is 2.0%–7.0%. The mass ratio of Group VIII metal oxides in the first co-active metal component to that in the second co-active metal component is 0.5–5.0:

1.

23. The catalyst according to any one of claims 20-22, characterized in that, The catalyst has a specific surface area of ​​170–190 m². 2 / g, with a pore volume of 0.55–0.85 mL / g; preferably, the catalyst has a specific surface area of ​​170–185 m² / g. 2 / g, with a pore volume of 0.65~0.80mL / g.

24. The catalyst according to any one of claims 20-22, characterized in that, The catalyst includes an additive selected from at least one of phosphorus, silicon, or boron, preferably phosphorus; Preferably, in the catalyst, the content of the auxiliary agent, calculated as oxide, is 2.0% to 6.0% based on the mass of the catalyst.

25. The application of the catalyst prepared by any of the preparation methods according to claims 1-19 or any of the catalysts according to claims 20-24 in the hydrotreating of heavy oil and residual oil.

Citation Information

Patent Citations

  • Residual oil hydrodemetallization catalyst, preparation and application thereof

    CN104646007A